Synthesis and antiviral evaluation of 2′, 2′, 3′, 3′-tetrafluoro nucleoside analogs. Issue 7 (15th February 2017) - Sari, Ozkan; Bassit, Leda; Gavegnano, Christina; McBrayer, Tamara R.; McCormick, Louise; Cox, Bryan; Coats, Steven J.; Amblard, Franck; Schinazi, Raymond F.
Graphical abstract: Highlights: The synthesis of novel 2′, 2′, 3′, 3′-tetrafluoro nucleoside analogs is described. Glycosylation reactions are achieved via Mitsunobu coupling. Energetics of ring conformation are compared to differently substituted ribose. Evaluation of Tetrafluoro nucleosides in vitro against a panel of DNA and RNA viruses. Abstract: Herein, we report the synthesis of novel 2′, 2′, 3′, 3′-tetrafluorinated nucleoside analogs along with their phosphoramidate prodrugs. A tetrafluoro ribose moiety was coupled with different Boc/benzoyl-protected nucleobases under Mitsunobu conditions. After deprotection, tetrafluorinated nucleosides13b, 14b, 20b -22b were reacted with phenyl-(isopropoxy-l -alaninyl)-phosphorochloridate to afford corresponding monophosphate prodrugs24b –28b . All synthesized compounds were evaluated against several DNA and RNA viruses including HIV, HBV, HCV, Ebola and Zika viruses.